FORECASTING AS A WAY TO REDUCE THE RISKS OF A CASH FLOW DEFICIT IN AGRICULTURAL ORGANIZATIONS - Alexey NOSOV; Olga TAGIROVA; Marina FEDOTOVA; Olga NOVICHKOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Cash is the most important resource, since an organization, if there are sufficient funds, can acquire everything that is necessary for carrying out production activities. The research was based on an agricultural organization that is engaged in the production of sugar beets and grain, as well as dairy and beef cattle breeding. Analysis of cash flows by direct, indirect and coefficient method showed that the company under study in the current year belongs to a “normal enterprise”, since it received a positive net cash flow from operating and financial activities and a negative one from investment. The calculated ratios of the efficiency of using the organization's funds over the past years have either increased or remained stable. To synchronize flows over time intervals and reduce the risks of a shortage of funds, the authors have developed cash flow forecasts for a year and a half by direct and indirect methods. Both plans showed that cash flow from current activities is positive, that is, the company's activities are profitable and generate income. The organization will be able to pay off the accumulated liabilities. The developed budgets will make it possible to predict the flow of cash flows of the enterprise, to control the synchronization of receipts and expenditures of funds, thereby maintaining their required volume to fulfill payment obligations.